Ethno-botanical study of the African star apple (Chrysophyllum albidum G. Don) in the Southern Benin (West Africa) - Houessou, Laurent G.; LOUGBEGNON, OLOU TOUSSAINT; GBESSO, François; ANAGONOU, Lisette E. S.; SINSIN, Brice (My University, 2012)
Background: In addition to plant species biology and ecology, understanding the folk knowledge systems related to the use of plant species and how this knowledge system influences the conservation of plant species is an important issue in the implementation of sustainable strategies of biodiversity conservation programs. This study aimed at providing information on the use and local knowledge variation on Chrysophyllum albidum G. Don a multipurpose tree species widely used in southern Benin. Methods: Data was collected through 210 structured interviews. Informants were randomly selected from ten villages. The fidelity level and use value of different plant parts of C. albidum were estimated. The variation in ethnobotanical knowledge was assessed by comparing the use value between ethnic, gender and age groups. In order to assess the use pattern of the different plant parts in folk medicine, a correspondence analysis was carried out on the frequency citation of plant parts. Results: Four categories of use (food, medicine, firewood and timber) were recorded for C. albidum. With respect to the different plant parts, the fleshy pulp of the African star apple fruit showed high consensus degree as food among the informants. Fifteen diseases were reported to be treated by the different parts of C. albidum in the region. Correspondence analysis revealed the specificity of each part in disease treatment. There was no significant difference among ethnic groups regarding the ethno-botanical use value of C. albidum. However, significant difference existed between genders and among age groups regarding the knowledge of the medical properties of this species. Conclusions: C. albidum is well integrated in the traditional agroforestry system of the southern Benin. Despite its multipurpose character, this species remains underutilized in the region. Considering the current threat of habitat degradation, action is needed in order to ensure the long term survival of the species and local communities’ livelihoods.
Keywords: Benin; Ethnobotanical knowledge variation; Use category; Underutilized species